Planning time in Relation to Complexity of the Writing Task Performance of EFL learners in Non-English Country: Case Study at English Department Khairun University, Indonesia - Hamka, Nurhadi (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2021)
Writing is a place to express feelings and thoughts in relatively permanent form. However, it becomes problematic because it requires certain linguistic features such as fluency, accuracy, and complexity, (the latter being the dependent variable for the study). One way to overcome these problems is through planning. Thus, this research is focused to find out the effect of planning on complexity in the writing performance especially in EFL learners. There are 20 final-year of undergraduate students of Unkhair involved and are selected through individual IELTS prediction writing-test. This study applies Independent t-test for the first variable of complexity: richness and diversity, and the second variable: size and elaborateness uses Wilcoxon-Mann-Whitney U test. The study uses two different groups as independent variables: 1) Planning group will be coded P1, P2, P3, … and so on, while 2) without planning group will be coded WP1, WP2, WP3, … and so on. The result of the study presents that the mean score in planning groups of both number of words per T-unit and number of clauses per T-unit are generally higher with 10.684 and 1.487, respectively, than in without planning group with just 9.403 and 1.225, respectively. The figures conclude that through planning which happened before the writing, helps the learners to accomplish a better performance regarding the number of words and clauses occur per T-unit.